Determinants of skilled birth attendant delivery among reproductive age women in Lesotho: A multilevel analysis of demographic and health survey data - Hiwot Tezera Endale; Tseganesh Asefa; Tiget Ayelgn Mengstie; Mihret Getnet; Helen Lamesgin Endalew; Amare Belete Getahun; Gashaw Dessie; Thomas Kidanemariam Yewodiaw; Engidaw Fentahun Enyew (PLoS ONE, 2026)
Background Skilled birth attendant (SBA) delivery, defined as childbirth assisted by trained healthcare professionals such as doctors, midwives, and nurses, is a cornerstone of the World Health Organization’s Safe Motherhood Initiative to reduce maternal mortality. Despite high SBA coverage in Lesotho, maternal mortality remains elevated. This study aimed to assess the determinants of SBA delivery among reproductive-age women in Lesotho using the 2023–2024 Lesotho Demographic and Health Survey data. Methods A cross-sectional study design was applied using nationally representative data of 1,407 women aged 15–49 years. Multilevel logistic regression models were employed. Adjusted odds ratios (AOR) and 95% confidence intervals (CI) were reported, with p-values <0.05 considered statistically significant. Results Skilled birth attendant (SBA) coverage was 91.8%. Women aged 35–49 had 60% lower odds of SBA delivery (AOR = 0.40; 95% CI: 0.17, 0.95). Higher maternal education (primary: AOR = 1.47; 95% CI: 1.02, 4.90; secondary: AOR = 1.63; 95% CI: 1.12, 2.94; and tertiary: AOR = 3.88; 95% CI: 2.50, 5.20), wealthier households (AOR = 4.30; 95% CI: 1.10, 16.80), and age at first birth between 20–24 years (AOR = 3.74; 95% CI: 1.77, 7.89) were positively associated with SBA delivery. Women initiating ANC in the third trimester had 63% lower odds of SBA use (AOR = 0.37; 95% CI: 0.14, 0.99). Conclusion Despite high SBA coverage in Lesotho, disparities exist, particularly among older women and late ANC initiators. Targeted policies such as community-based health education programs, transport support for rural women, mobile health reminders, incentives for facility deliveries, and the deployment of skilled birth attendants in underserved areas are vital to improving access, promoting education, encouraging early ANC engagement, and ultimately enhancing SBA utilization to reduce maternal mortality.